An innovative Indigenous-led model for integrated COVID-19 case management in Auckland, New Zealand: lessons from implementation - Curtis, Elana; Loring, Belinda; Latham, Kadin; Jordan, Anthony; Chee, Nigel; Hunia, Rangimarie; Snowden, Karl; Tari, Kerry; Murupaenga, Paora; Tipene, Roimata; Whitcombe, Stevie; Embers, Kelleigh; et al. (Frontiers in Public Health, 2024)
In Aotearoa/New Zealand (NZ), the Indigenous Māori population have been more severely impacted than non-Māori throughout the COVID-19 pandemic, and less well served by NZ’s COVID-19 response. This case-study describes an innovative Indigenous-led service delivery model, which was designed and implemented to improve the case and contact management of Māori with COVID-19 in Auckland. We outline the context in which the conventional public health case and contact management was failing Māori and the factors which enabled Indigenous innovation and leadership. We describe the details of the model and how the approach fundamentally differed to the conventional approach to care. Qualitative and quantitative data on impact of the model are shared, along with the key barriers and enablers in the implementation of the model. The Māori Regional Coordination Hub (MRCH) model offers a valuable alternative to the conventional public health case and contact management approach, and this case study highlights lessons which may be applicable to improving the design and delivery of public health services to other Indigenous and marginalized groups.